2003
DOI: 10.1046/j.1095-8339.2003.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric, AFLP and plastid microsatellite variation in populations of Scalesia divisa and S. incisa (Asteraceae) from the Galápagos Islands

Abstract: Scalesia divisa and S. incisa (Asteraceae), both endemic to the Galápagos Islands, are found only on San Cristóbal, where S. divisa grows in the north‐west of the island while S. incisa occurs in the north‐east. At localities in between, populations with deviating individuals occur. Here we analyse the population structure of S. divisa, S. incisa and two deviating populations based on morphology, AFLP markers and two plastid microsatellite loci. The deviating populations were collected from either side of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 31 publications
3
32
1
1
Order By: Relevance
“…The method was modified in accordance with Nielsen et al (2003) to use fluorescent EcoRI primers from TAG Copenhagen A/S rather than radioactive primers. PCR amplifications were carried out in a PTC 200 Peltier Thermal Cycler (MJ Research).…”
Section: Aflp Fingerprintingmentioning
confidence: 99%
See 2 more Smart Citations
“…The method was modified in accordance with Nielsen et al (2003) to use fluorescent EcoRI primers from TAG Copenhagen A/S rather than radioactive primers. PCR amplifications were carried out in a PTC 200 Peltier Thermal Cycler (MJ Research).…”
Section: Aflp Fingerprintingmentioning
confidence: 99%
“…From this the genus of 15 known species, which are all tetraploid, has evolved (Eliasson 1974). Nielsen et al (2003) suggested that Scalesia incisa Hook. f. and Scalesia divisa Andersson on San Cristó bal hybridize, and on Santa Cruz, Eliasson (1974) reported intermediate specimens between Scalesia pedunculata Hook.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In wild (Nielsen et al, 2003) as well as in cultivated (Roldán-Ruiz et al, 2001) plants, low concordance has been reported between molecular and phenotypic genetic divergence. This scenario is commonly reported, except when the molecular markers used are closely linked to the genes controlling the morphological characteristics analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario is commonly reported, except when the molecular markers used are closely linked to the genes controlling the morphological characteristics analyzed. Nielsen et al (2003) applied discriminant analysis to 6 natural populations from the genus Scalesia and found an increase in the discrimination of individuals in 5 of these populations using AFLP markers compared with using morphometric data.…”
Section: Discussionmentioning
confidence: 99%